Music Composition Today - Ming Tsao (Revista Vortex, 2020)
In this essay, composer Ming Tsao presents a critical overview of today's new music scene, with a special emphasis on the task of teaching music composition today and the culture of new music festivals. Tsao's main critique delves into the current tendency towards entertainment predominantly displayed in some German new music festivals, commonly advertised as experimental music. Alongside this critique, Tsao presents Steven Takasugi's musical theater work “Side Show” (2009-15) as an example of today's music composition that resists this emerging commercialism in concert music. In this text, Tsao makes reference to the writings and ideas of German composer Helmut Lachenmann, mainly on his concepts of Geräuschmusik, Kadenzklänge, Texturklänge, and the language-like aspects of music, as well as to the writings of poet J. H. Prynne [note by editor].